Handover Management In Mobile Satellite Communications - Sali, Aduwati (2002)
Mobile satellite communication offers vast coverage area with moderate bandwidth demands. However, in mobile satellite communication using Low Earth Orbits (LEO) satellite service, handover frequently occurs due to high velocity and large number of mobile satellites. With increase demand of multimedia traffic, an optimum utilization of network resources has been investigated. To accommodate and maintain Quality of Service (QoS) of handover calls in mobile satellite communication, priority for handover calls are applied. Traffic parameters of traffic arrival rate, traffic duration and priority among traffic applications are introduced. Traffic applications of type voice, video and data are observed and analysis of traffic behavior on handover has been done. An optimum set of channels to serve the different traffic types is proposed after considering the handover initiation and handover execution criteria. The algorithm proposes a more accurate measurement of handover initiation angle, introduced as look-up angle, which further reduces handover rate and successfully conserve the network resources.